Suatu Gagasan tentang Peternakan Masa Depan dan Strategi Mewujudkannya - Yusmichad Yusdja; Nyak Ilham (Forum penelitian Agro Ekonomi, 2007)
EnglishThis paper discusses an idea on future livestock and how to bring the idea into reality.  The sources of the paper are taken from various livestock research results along with the overview of relevant economics theories.  Based on these sources, it is concluded that the future livestock could be designed and could also be materialized.  However, the government should not recklessly encourage the community to move forward and directly allocate the existing resources.  Instead, the government should allow the community to design future livestock by themselves through free market mechanims.  On the other hand, government policies should be directed to focus on servicess and draw positive responses to basic livestock problems to enhance market mechanisms.  Old paradigm saying that livestock business is a employment opportunity for the community should no longer used and should be changed to a new paradigm saying that livestock business has a function to encourage agroindustry development for a more open and widen employment and business opportunities. The implication of this idea is that the government is suggested to design a national livestock development roadmap with its details in livestock development region of each regencies.  This roadmap will be very helpful in program development preparation which also encourage the autonomous inter-regency cooperation.  IndonesianTulisan ini merupakan sebuah gagasan tentang peternakan masa depan dan strategi mewujudkannya. Sumber bahan untuk penulisannya adalah hasil-hasil penelitian peternakan dan pandangan-pandangan teori ekonomi yang relevan. Dari review hasil penelitian serta teori ekonomi dan kebijakan pertanian dapat disimpulkan bahwa peternakan masa depan dapat saja didisain bagaimana ujudnya. Namun demikian, pemerintah tidak dapat begitu saja menggerakan masyarakat dan mengatur alokasi sumberdaya secara langsung. Atas dasar itu, pemerintah lebih baik menyerahkan pada masyarakat bagaimana peternakan masa depan itu melalui mekanisme pasar yang bebas. Pada sisi lain, kebijakan pemerintah sebaiknya fokus pada pelayanan dan membangun simpul-simpul permasalahan dasar peternakan saja sehingga mekanisme pasar dapat diaktifkan. Paradigma lama yang mengatakan bahwa usaha peternakan merupakan lapangan kerja masyarakat haruslah diganti dengan paradigma baru yakni peternakan haruslah berfungsi mendorong pembangunan dan perkembangan agroindustri sehingga terbuka luas kesempatan kerja dan usaha. Implikasi kebijakan dari gagasan ini adalah perlu dibuat roadmap pembangunan peternakan secara nasional dan diuraikan secara rinci di setiap kabupaten wilayah pengembangan ternak. Roadmap akan membantu mengarahkan penyusunan program-program pembangunan dan mendorong kerjasama antar daerah otonom.